2020
DOI: 10.1177/2325967120915857
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Stem Cell Therapy for Tendon Disorders: A Systematic Review

Abstract: Background: Stem cell therapy is an emerging treatment for tendon disorders. Purpose: To systematically review the efficacy of stem cell therapy for patients with tendon disorders. Study Design: Systematic review; Level of evidence, 4. Methods: MEDLINE/PubMed, EMBASE, CINAHL, CENTRAL, PEDro, and SPORTDiscus; trial registers; and gray literature were searched to identify randomized controlled trials (RCTs) and non-RCTs, cohort studies, and case series with 5 or more cases. Studies investigating any type of stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Arrays of potential cellular sources have therefore been proposed in tendon bioengineering workflows, comprising various stem cells, placenta cells, amniotic cells, platelet-derivatives, tendon sheath fibroblasts, and adult tenocytes. However, results have been variable and sometimes contradictory [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Recently, cultured primary human fetal progenitor tenocytes (hFPT) have been preliminarily investigated within allogeneic homologous regenerative medicine approaches of tendon ruptures (e.g., hand, Achilles, or rotator cuff tendons) or specific inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Arrays of potential cellular sources have therefore been proposed in tendon bioengineering workflows, comprising various stem cells, placenta cells, amniotic cells, platelet-derivatives, tendon sheath fibroblasts, and adult tenocytes. However, results have been variable and sometimes contradictory [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Recently, cultured primary human fetal progenitor tenocytes (hFPT) have been preliminarily investigated within allogeneic homologous regenerative medicine approaches of tendon ruptures (e.g., hand, Achilles, or rotator cuff tendons) or specific inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews published in 2017 and 2020 documented the positive therapeutic effect of orthobiologics on tendon injuries in humans. Clinical improvement and in some studies structural changes detected by MRI and US were reported ( 31 , 32 ). Positive effects were maintained even 3 to 4 years after the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…BM-MSCs promote early rehabilitation, lower incidence of re-rupture, improvement of pain scores, and amelioration of tendon structure and strength, without the occurrence of serious complications [ 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. van den Boom et al derived level 4 evidence for BMAC augmentation in Achilles tendon repair in terms of improved PROMs and absence of re-tears in 2.5 years follow-up [ 88 ]. However, more robust data are still required to further support the efficacy and safety regarding the clinical administration of BMA for AT, more specifically.…”
Section: Orthobiologics In Atmentioning
confidence: 99%